If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 5 = 11x + -3 Reorder the terms: 5 + 13x = 11x + -3 Reorder the terms: 5 + 13x = -3 + 11x Solving 5 + 13x = -3 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 5 + 13x + -11x = -3 + 11x + -11x Combine like terms: 13x + -11x = 2x 5 + 2x = -3 + 11x + -11x Combine like terms: 11x + -11x = 0 5 + 2x = -3 + 0 5 + 2x = -3 Add '-5' to each side of the equation. 5 + -5 + 2x = -3 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = -3 + -5 2x = -3 + -5 Combine like terms: -3 + -5 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 7b^2=231 | | 6x^2+36=0 | | 7x+5=-x-3 | | 2(7-2n)+3(n-2)=4(n+6) | | 25x-3=24+2 | | 9x-9=56 | | 2x+8=5-4x | | 4x+32=10x+10 | | 7x-24=32 | | 5a^2-26a=24 | | (d+7)(d-7)= | | 4+y^2+5y=0 | | 182=21m | | 0.6(y+3)=48 | | A=2lw+2lh+2wh | | 2x^2-2xy+y^2-4x+2y+1=0 | | 3x-5=13x-5 | | 7x-2=3x+8 | | 7(3x-5)=5(3x-8) | | 7x+3=158 | | 2x-3=6x+4x | | -32y^2-24y=0 | | ax=bx-3y+5 | | (6x-2)=3(x+1)+6 | | .25y+6=.2y | | 7x-(2x+4)=1 | | 5w^2-5W=0 | | 4+7(x-1)=7-2(x-2) | | b^2+6b=0 | | 6x+3=-(x-31) | | a(x)+b=c(x)+d | | ax+b=cx+d |